KEKERASAN DALAM RUMAH TANGGA SEBAGAI DASAR DAN ALASAN PERCERAIAN - Annisa Putri Utami; Nanik Sutarni; Burham Pranawa (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2025)
Indonesia is a state of law that guarantees protection for all its citizens, including within the institution of marriage. Domestic violence (KDRT) has become a phenomenon that disrupts family harmony and is often the basis for divorce lawsuits, particularly from wives. However, public understanding of domestic violence as a legitimate legal reason for divorce remains low. This study uses a normative and empirical juridical approach, through literature studies and interviews at the Boyolali Religious Court. The findings indicate that domestic violence can legally be used as the basis for divorce, as stated in Article 19 (d) and (f) of Government Regulation No. 9 of 1975 and Article 116 of the Compilation of Islamic Law. Evidence in divorce cases involving domestic violence can include witness testimonies, medical reports (visum et repertum), and reports to law enforcement. In conclusion, legal awareness and protection for victims of domestic violence must continue to be strengthened through education and a justice system that sides with victims.